Konstruksi Bangunan Sederhana dan Tahan Gempa SDN 7 Sape Kabupaten Bima - Dewandha Mas Agastya; Fera Fitri Salsabila; Nyoman Merdana; Pathurahman; Evrianti Syntia Dewi; Hariyadi; Ni Nyoman Kencanawati (Jurnal Atma Inovasia, 2026)
Bima Regency is an area with significant earthquake risk, making the application of earthquake – resistant construction principles in educational facilities essential. However, the understanding of construction workers and the local community regarding technical standards for earthquake – resistant buildings is still limited. This community service activity aimed to improve knowledge and implementation of simple earthquake – resistant construction principles in school facility development at SD Negeri 7 Sape, Bima Regency. The methods included socialization activities on the technical requirements of earthquake – resistant buildings followed by direct supervision and assistance during construction work. The materials delivered covered building material quality, structural dimensions and elements, structural connections, and construction workmanship quality. The results showed an improvement in workers and community members understanding of earthquake – resistant construction principles and better application of structural details, such as proper stirrup spacing, adequate concrete cover, and the use of 135˚ stirrup hooks. The activity also increased awareness regarding the importance of material quality and accuracy in construction work. Therefore, this community service program contributes positively to improving the quality of simple earthquake – resistant buildings and supports disaster risk education efforts in educational facilities.